Separator for power storage device, and power storage device

By using a porous layer composed of polyolefin resin and ionic compounds in the separator of the secondary battery of lithium ion, the problem of efficient battery performance is achieved to solve the problem of loss of insulation loss at high temperature segmentation at high temperature.

CN114335893BActive Publication Date: 2025-01-28ASAHI KASEI BATTERY SEPARATOR CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202210042534.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-11-10
Filing Date
2018-11-09
Publication Date
2025-01-28
Estimated Expiration
2038-11-09

AI Technical Summary

Technical Problem

In the prior art, polyethylene may melt and flow at high temperatures in the separator of lithium-ion secondary batteries, resulting in loss of insulation, and metal oxide fillers may cause polyolefin deterioration and battery safety problems.

Method used

The porous layers containing polyolefin resin and ionic compounds are used as septum parts. By adjusting the thickness, pore rate and ionic compounds of the porous layer, the heat resistance and ionic viaing of the separators and ions are increased.

Benefits of technology

The heat resistance of the separator at high temperature and the transmission of ions are achieved, avoiding the deterioration of polyolefins, and improving the safety and input and output characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003470894590000341
    Figure BDA0003470894590000341
  • Figure BDA0003470894590000351
    Figure BDA0003470894590000351
Patent Text Reader

Abstract

The present invention relates to a separator for an electric storage device and an electric storage device, wherein the separator has a porous layer containing a polyolefin resin and an ionic compound, wherein the content of the ionic compound in the porous layer is 5 mass % or more and 99 mass % or less, and the whiteness of the separator exceeds 98.0.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of an application with a filing date of November 9, 2018, an application number of 201880014565.1, and an invention name of separator for power storage device, and power storage device. Technical Field

[0002] The present invention relates to a separator for an electric storage device and an electric storage device using the separator. Background Art

[0003] Power storage devices are used in a wide range of applications such as power supplies for consumer equipment, vehicle-mounted power supplies, and stationary power supplies. Among these power storage devices, lithium-ion secondary batteries have excellent characteristics such as high energy density and high durability, and therefore have been rapidly used as power supplies for electric vehicles in recent years.

[0004] Lithium-ion secondary batteries generally use polyolefin microporous membranes as separators. The separator is placed between the positive electrode and the negative electrode to prevent direct contact or short circuit between the positive and negative electrodes and to allow ion conduction through the electrolyte retained in the microporous membrane.

[0005] The power storage device for electric vehicles is frequently charged and discharged with a large current in a short time, such as rapid charging and regenerative braking, and therefore needs to have a high input-output characteristic. Furthermore, the power storage device is often arranged at a high density relative to the limited space in the vehicle, so the temperature of the battery is easily increased. From the perspective of ensuring safety, a high level of heat resistance is required for the separator.

[0006] In recent years, various attempts have been made to improve the heat resistance of separators. The most common method is to use a polyolefin microporous membrane as a substrate and form a heat-resistant layer containing an inorganic filler and / or a heat-resistant organic resin as a main body on the substrate. For example, in Patent Document 1, a heat-resistant layer containing silicon dioxide as a main body is formed on a polyethylene microporous membrane to improve the heat resistance of the separator.

[0007] On the other hand, a method for increasing the heat resistance of the polyolefin microporous membrane itself has also been proposed. For example, Patent Document 2 discloses the use of a polyethylene resin and alumina in combination to produce a polyethylene microporous membrane containing alumina. Patent Document 2 specifically describes a microporous membrane formed of high-density polyethylene and alumina particles (average particle size 2 nm), which can maintain insulation even at high temperatures through the alumina particles.

[0008] In addition, a method of producing a polyethylene microporous membrane containing silica by combining a polyethylene resin and silica is also proposed in Patent Documents 3 and 4. Specifically, Patent Documents 3 and 4 describe that by filling a polyethylene resin with silica at a high concentration, shrinkage of the microporous membrane can be suppressed even at a high temperature exceeding the melting point of polyethylene.

[0009] Furthermore, a method for preparing a polyolefin microporous membrane containing barium sulfate by mixing a polyolefin resin and barium sulfate is disclosed in Patent Document 5. Specifically, a polyolefin resin such as high-density polyethylene and soft polypropylene is mixed with barium sulfate (average particle size 660 nm) as a filler, and the resulting mixture is stretched to thereby peel off the interface between the resin and the filler to form a porous membrane.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: International Publication No. 2012 / 005139

[0013] Patent Document 2: Japanese Patent Application Laid-Open No. 10-50287

[0014] Patent Document 3: International Publication No. 2010 / 108148

[0015] Patent Document 4: Japanese Patent Application Publication No. 2010-262785

[0016] Patent Document 5: Japanese Patent Application Publication No. 2005-71979 Summary of the invention

[0017] Problem that the invention aims to solve

[0018] However, the technology described in Patent Document 1 uses a polyethylene microporous film as the substrate of the heat-resistant layer, so there is a possibility that the polyethylene melts and flows at high temperatures, and the insulation of the separator cannot be maintained. In addition, this technology requires a manufacturing process of the substrate and a forming process of the heat-resistant layer, so the number of processes is large, and there is also a problem of low productivity.

[0019] In addition, the technologies described in Patent Documents 2 to 4 require that the polyolefin and the metal oxide be kneaded at high temperature because the polyolefin microporous membrane contains a metal oxide filler. If the polyolefin is brought into contact with the metal oxide at high temperature, the polyolefin may be degraded and the separator may turn yellow due to the metal oxide. Degraded polyolefin is not preferred from the perspective of improving the reliability and safety of the power storage device due to concerns about voltage resistance and oxidation resistance. In addition, in a high-temperature power storage device, the metal oxide and the electrolyte may react, which is not preferred from the perspective of damaging battery characteristics such as cycle characteristics or damaging safety due to battery expansion caused by gas generation.

[0020] The technology described in Patent Document 5 makes the membrane porous by exfoliating the interface between the polyolefin resin and the filler. If the particle size of the filler is large, large-pore gaps are likely to be generated occasionally, and when the membrane is used as a separator of a power storage device, micro short circuits or self-discharge may occur. In addition, fillers with large particle sizes are mostly manufactured by crushing minerals quarried naturally, and contain impurities such as metal oxides and halogen elements, so they may promote the degradation of polyolefins and cause the separator to turn yellow.

[0021] The present invention has been made in view of the above problems, and an object of the present invention is to provide a separator for an electric storage device which has excellent heat resistance and ion permeability, does not impair the durability of the electric storage device, and has little degradation of polyolefin, and an electric storage device including the separator.

[0022] Solutions for solving problems

[0023] The present inventors have conducted intensive studies to achieve the above object and have found that a separator for a power storage device having a porous layer containing a polyolefin resin and an ionic compound and having a specific whiteness can solve the above problems, thereby completing the present invention.

[0024] That is, the present invention is as follows.

[0025] [1] A separator for a power storage device, comprising a porous layer containing a polyolefin resin and an ionic compound, wherein the content of the ionic compound in the porous layer is 5 mass % or more and 99 mass % or less, and the separator has a whiteness exceeding 98.0.

[0026] [2] The separator for a power storage device according to [1], wherein the separator has a whiteness of 98.5 or more and 105 or less.

[0027] [3] The separator for a power storage device according to [1] or [2], wherein the content of the ionic compound in the porous layer is 5% by mass or more and less than 50% by mass.

[0028] [4] The separator for a power storage device according to [1] or [2], wherein the content of the ionic compound in the porous layer is 86 mass % or more and 99 mass % or less.

[0029] [5] The separator for a power storage device according to any one of [1] to [4], wherein the polyolefin resin contains polyethylene having a viscosity average molecular weight of 600,000 to 5,000,000.

[0030] [6] The separator for a power storage device according to any one of [1] to [5], wherein the content of the metal oxide in the separator for a power storage device is 10% by mass or less.

[0031] [7] The separator for a power storage device according to any one of [1] to [6], wherein the ionic compound has one or more anions selected from the group consisting of sulfate ions, nitrate ions, phosphate ions, and halide ions.

[0032] [8] The separator for a power storage device according to any one of [1] to [7], wherein the ionic compound has one or more cations selected from the group consisting of alkali metal ions and alkaline earth metal ions.

[0033] [9] The separator for a power storage device according to any one of [1] to [8], wherein the ionic compound is barium sulfate.

[0034]

[10] The separator for a power storage device according to any one of [1] to [9], wherein the average particle size of the ionic compound is 5 nm or more and 600 nm or less.

[0035]

[11] The separator for an electric storage device according to any one of [1] to

[10] , wherein the average pore diameter of the separator for an electric storage device is 10 nm or more and 100 nm or less.

[0036]

[12] The separator for an electric storage device according to any one of [1] to

[11] , wherein the air permeability of the separator for an electric storage device is 10 sec / 100 ml or more and 500 sec / 100 ml or less.

[0037]

[13] The separator for an electric storage device according to any one of [1] to

[12] , wherein the puncture strength of the separator for an electric storage device is 100 gf or more and 600 gf or less.

[0038]

[14] The separator for an electrical storage device according to any one of [1] to

[13] , wherein the polyolefin resin contained in the separator for an electrical storage device has a viscosity average molecular weight of 300,000 to 5,000,000.

[0039]

[15] An electricity storage device comprising a positive electrode, a negative electrode, and the separator for an electricity storage device according to any one of [1] to

[14] .

[0040] Effects of the Invention

[0041] According to the present invention, a separator for an electric storage device having excellent heat resistance and ion permeability, which does not impair the durability of an electric storage device and has little degradation of polyolefin, and an electric storage device including the separator can be provided. DETAILED DESCRIPTION

[0042] The following is a detailed description of a mode for implementing the present invention (hereinafter referred to as "this embodiment"). It should be noted that the present invention is not limited to the following embodiment, and various modifications can be made within the scope of the gist of the present invention.

[0043] 《Porous Layer》

[0044] The separator for the power storage device of the present embodiment has a porous layer containing a polyolefin resin and an ionic compound. The porous layer is used in combination with the polyolefin resin and the ionic compound, so that the power storage device will not deteriorate, the heat resistance and ion permeability of the separator are improved, and the safety and input-output characteristics of the power storage device are improved.

[0045] The thickness of the porous layer is preferably 1 μm or more, more preferably 2 μm or more, and further preferably 3 μm or more. When the thickness of the porous layer is 1 μm or more, the heat resistance of the separator is improved. In addition, the thickness of the porous layer is preferably 20 μm or less, more preferably 18 μm or less, and further preferably 16 μm or less. When the thickness of the porous layer is 20 μm or less, the energy density of the power storage device can be increased.

[0046] The porosity of the porous layer is preferably 30% or more, more preferably 35% or more, and further preferably 40% or more from the viewpoint of improving the ion permeability of the separator. On the other hand, from the viewpoint of maintaining the structural stability of the separator, it is preferably 70% or less, more preferably 65% ​​or less, and further preferably 60% or less.

[0047] The thickness ratio of the porous layer in the entire storage separator is preferably greater than 0% and less than 100%, more preferably greater than 10% and less than 100%, and further preferably greater than 20% and less than 100%, taking into account the heat resistance, ion permeability, and physical strength of the separator. If the thickness ratio of the porous layer is 100%, manufacturing becomes easy, so it is preferred. On the other hand, even if the thickness ratio of the porous layer is less than 100%, the high heat resistance of the porous layer can be imparted to the separator as a whole, so it can be less than 100%.

[0048] There is no particular limitation on the method for making the porous layer, and various methods can be used. Specifically, stretching processes such as uniaxial stretching and biaxial stretching can be used; processes for removing third components other than polyolefin resins and ionic compounds by extraction, volatilization, decomposition, etc. can be used. As the third component, liquid paraffin, dioctyl phthalate and other plasticizers can be used alone or in combination; solvents such as acetone and water; inorganic substances such as calcium carbonate and silicon dioxide. As a method for making a porous layer, from the perspective of reducing the manufacturing cost of the separator and improving the uniformity of the film thickness, it is preferred to have at least a stretching process, more preferably a stretching process and a third component removal process, further preferably a stretching process and a third component extraction process, and particularly preferably a biaxial stretching process and a plasticizer extraction process. If these methods are used to make a porous layer, not only can the porous layer be formed uniformly, but also the thickness, porosity and other physical properties of the separator for the storage device as a whole can be easily adjusted.

[0049] 《Polyolefin resin》

[0050] The separator for the storage device of the present embodiment has a porous layer containing a polyolefin resin. The polyolefin resin used in the present embodiment refers to a polyolefin resin used in conventional extrusion, injection, inflation, and blow molding, and is a polymer containing an olefin as a monomer component, such as a homopolymer, copolymer, and multi-stage polymer of ethylene, propylene, 1-butene, 2-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene. In addition, polyolefins selected from the group consisting of these homopolymers, copolymers, and multi-stage polymers can also be used alone or in combination.

[0051] Specific examples of the polyolefin resin include low-density polyethylene (density 0.910 g / cm 3 More than and less than 0.930g / cm 3 ), linear low-density polyethylene (density 0.910g / cm 3 Above 0.940g / cm 3 Below), medium density polyethylene (density 0.930g / cm 3 More than and less than 0.942g / cm 3 ), high-density polyethylene (density 0.942g / cm 3 Above), ultra-high molecular weight polyethylene (density 0.910g / cm 3 Above 0.970g / cm 3 Below), isotactic polypropylene, syndiotactic polypropylene, atactic polypropylene, polybutene, polymethylpentene, ethylene propylene rubber.

[0052] The ratio of polyolefin resin in the porous layer is preferably more than 0 mass %, more preferably more than 1 mass %, and further preferably more than 2 mass %. When the ratio of polyolefin resin exceeds 0 mass %, not only the formation of the porous layer becomes easy but also physical strength can be given to the porous layer. In addition, the ratio is preferably less than 95 mass %, more preferably less than 90 mass %, and further preferably less than 85 mass %. When the ratio of polyolefin resin is less than 95 mass %, there is a tendency that the heat resistance of the porous layer increases.

[0053] The ratio of the polyolefin resin to the overall separator for the storage device is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more. When the ratio of the polyolefin resin is 5% by mass or more, sufficient physical strength can be given to the separator. In addition, the ratio is preferably 95% by mass or less, more preferably 90% by mass or less, and further preferably 85% by mass or less. When the ratio of the polyolefin resin is 95% by mass or less, there is a tendency for the heat resistance of the separator to increase.

[0054] The polyolefin resin preferably contains high-density polyethylene. The ratio of high-density polyethylene in the polyolefin resin is preferably 10% by mass or more, more preferably 35% by mass or more, further preferably 50% by mass or more, and may be 100% by mass. When the ratio of high-density polyethylene in the polyolefin resin is 10% by mass or more, the strength of the separator increases due to the mutual entanglement of high-density polyethylene molecular chains.

[0055] In addition, the polyolefin resin preferably contains high molecular weight polyethylene. The ratio of high molecular weight polyethylene in the polyolefin resin is preferably 30% by mass or more, more preferably 50% by mass or more, further preferably 65% ​​by mass or more, and may be 100% by mass. The viscosity average molecular weight (Mv) of the high molecular weight polyethylene is preferably 600,000 or more and 5,000,000 or less, more preferably 650,000 or more and 4,000,000 or less, and further preferably 700,000 or more and 3,000,000 or less. The viscosity average molecular weight can be obtained by measuring the intrinsic viscosity of the decalin solvent at 135°C based on ASTM-D4020, and calculating it by the calculation formula corresponding to the polyolefin resin.

[0056] For polyethylene, Mv can be calculated by the following formula.

[0057] [η] = 6.77 × 10 -4 Mv 0.67

[0058] For polypropylene, Mv can be calculated by the following formula.

[0059] [η] = 1.10 × 10 -4 Mv 0.80

[0060] It is preferred to use a polyolefin resin having a viscosity average molecular weight of 600,000 or more from the viewpoint of maintaining high melt tension and ensuring good moldability when the polyolefin resin composition is melt-kneaded, and from the viewpoint of providing sufficient mutual entanglement of the molecules of the polyolefin resin and improving the strength of the separator. On the other hand, it is preferred to adjust the viscosity average molecular weight to 5,000,000 or less from the viewpoint of improving the stability of the extrusion molding of the polyolefin resin.

[0061] From the viewpoint of improving the heat resistance of the separator, the polyolefin resin preferably contains polypropylene. The ratio of polypropylene in the polyolefin resin is preferably 1% by mass or more, more preferably 5% by mass or more, and further preferably 15% by mass or more. In addition, the ratio of polypropylene in the polyolefin resin is preferably 30% by mass or less, more preferably 20% by mass or less, and further preferably 10% by mass or less. It is preferred to adjust the ratio of polypropylene to 1% by mass or more, from the viewpoint of improving the heat resistance of the separator. On the other hand, from the viewpoint of improving the uniformity of the separator, the ratio of polypropylene is preferably 30% by mass or less.

[0062] The polyolefin resin used in the present embodiment can be mixed with phenolic, phosphorus, sulfur and other antioxidants; metal soaps such as calcium stearate and lithium stearate; and additives such as ultraviolet absorbers, light stabilizers, antistatic agents, antifogging agents, and coloring pigments as needed without impairing the advantages of the present invention.

[0063] 《Ionic Compounds》

[0064] The separator for a power storage device of the present embodiment has a porous layer containing an ionic compound. The ionic compound used in the present embodiment refers to a compound that is electrically neutral based on a chemical bond with high ionic bonding and includes a combination of one or more cations and one or more anions.

[0065] As ionic compounds, there are no particular limitations as long as they include a combination of cations and anions, and examples thereof include sulfates such as lithium sulfate, sodium sulfate, magnesium sulfate, calcium sulfate, barium sulfate, and aluminum sulfate; nitrates such as lithium nitrate, sodium nitrate, magnesium nitrate, and potassium nitrate; phosphates such as lithium phosphate, sodium phosphate, magnesium phosphate, and potassium phosphate; halides such as lithium fluoride, sodium chloride, and sodium bromide; carbonates such as lithium carbonate, sodium carbonate, and sodium bicarbonate; hexafluorophosphates such as lithium hexafluorophosphate; tetrafluoroborates such as lithium tetrafluoroborate; and perchlorates such as lithium perchlorate.

[0066] Regarding the anion of the ionic compound, if both the stability and cost inside the storage device are taken into consideration, it is preferably at least one selected from the group consisting of sulfate ions, nitrate ions, phosphate ions and halide ions, more preferably at least one selected from the group consisting of sulfate ions, phosphate ions and halide ions, further preferably sulfate ions and / or phosphate ions, and particularly preferably sulfate ions.

[0067] In addition, the cation of the ionic compound is preferably at least one selected from the group consisting of alkali metal ions and alkaline earth metal ions, more preferably lithium ions, sodium ions, potassium ions, magnesium ions, calcium ions, strontium ions or barium ions, further preferably magnesium ions, calcium ions or barium ions, and particularly preferably barium ions, in view of the stability inside the power storage device. That is, as an ionic compound, barium sulfate is most preferred from the perspective of the stability inside the power storage device.

[0068] In addition, the ionic compound can be used alone or in combination of two or more.

[0069] The shape of the ionic compound includes plate, scale, needle, column, spherical, polyhedral, block, etc., and a plurality of ionic compounds having the above shapes may be used in combination. The shape of the ionic compound is not particularly limited, but from the viewpoint of improving heat resistance, a columnar, spherical or polyhedral shape is preferred, and a spherical shape is more preferred.

[0070] Carbonates such as calcium carbonate have been commonly used as fillers for various polymers since ancient times, and their performance as fillers has been confirmed in various applications. However, in the special environment inside the power storage device, there is a possibility that carbonates will decompose and produce carbon dioxide, so it is not preferred. Ionic compounds other than carbonates such as sulfates, phosphates, and halides are preferred because they have high stability inside the power storage device.

[0071] It is known that metal oxides such as aluminum oxide have higher covalent bonding than ionic bonding as the nature of their chemical bonds. Therefore, in the present invention, aluminum oxide, boehmite, silicon dioxide, titanium dioxide, yttrium oxide, zirconium oxide, lithium oxide, sodium oxide, potassium oxide, magnesium oxide, calcium oxide, vanadium oxide, chromium oxide, manganese oxide, iron oxide, cobalt oxide, nickel oxide, copper oxide, zinc oxide and cerium oxide are classified as metal oxides and are not included in ionic compounds. In addition, compounds containing multiple metal oxides such as potassium titanate (K2O·8TiO2) are also classified as metal oxides.

[0072] The content of the metal oxide in the separator for a power storage device is preferably 10% by mass or less, more preferably 8% by mass or less, further preferably 6% by mass or less, and particularly preferably 4% by mass or less. This tends to suppress the promotion of polyolefin degradation.

[0073] The ratio of the ionic compound in the porous layer (i.e., the content of the ionic compound in the porous layer) is 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more. When the ratio of the ionic compound is 5% by mass or more, there is a tendency for the heat resistance of the porous layer to improve, but from the viewpoint of ensuring sufficient heat resistance in practical use, it is preferably 86% by mass or more, more preferably 90% by mass or more, and further preferably 95% by mass or more. On the other hand, from the viewpoint of maintaining physical strength while improving the ion permeability of the porous layer, it is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more.

[0074] In addition, the ratio is 99% by mass or less, more preferably 98.5% by mass or less, and further preferably 98% by mass or less. When the ratio of the ionic compound is 99% by mass or less, not only the formation of the porous layer becomes easy, but also the physical strength can be given to the porous layer. On the other hand, from the viewpoint of further improving the physical strength of the porous layer, it is preferably 50% by mass or less, more preferably 45% by mass or less, and further preferably 40% by mass or less.

[0075] The ratio of the ionic compound to the overall separator for the storage device is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more. When the ratio of the ionic compound to the overall separator is 5% by mass or more, there is a tendency for the heat resistance of the separator to be improved. In addition, the ratio is preferably 95% by mass or less, more preferably 90% by mass or less, and further preferably 85% by mass or less. When the ratio of the ionic compound to the overall separator is 95% by mass or less, there is a tendency to prevent the ionic compound from falling off the separator.

[0076] The specific gravity of the ionic compound is usually higher than that of the polyolefin resin, so it is sometimes appropriate to record the ratio of the ionic compound in the separator in volume % rather than mass %. The above ratio is preferably 2 volume % or more and 90 volume % or less, more preferably 5 volume % or more and 80 volume % or less, and further preferably 8 volume % or more and 70 volume % or less. When the ratio of the ionic compound is 2 volume % or more, there is a tendency to improve the heat resistance of the separator. In addition, when the ratio of the ionic compound is 90 volume % or less, there is a tendency to prevent the ionic compound from falling off the separator.

[0077] The average particle size of the ionic compound is preferably 5 nm or more and 600 nm or less, more preferably 10 nm or more and 500 nm or less, and further preferably 20 nm or more and 400 nm or less. The average particle size refers to the average value of the particle sizes of the ionic compound at 10 points that can be confirmed in the field image when the porous layer is observed with a scanning electron microscope at 30,000 times. When calculating the average particle size, the particle size of each particle in a state where it exists alone is used, and when the particles are aggregated, the particle size of the primary particles constituting the aggregate is used.

[0078] If the average particle size of the ionic compound is 5 nm or more, the film thickness and pore distribution of the separator are uniform, and the input-output characteristics of the power storage device are improved. In addition, if the average particle size is 600 nm or less, the pore size of the separator is uniform, and it is less likely to produce local large pores, thereby improving the safety of the power storage device.

[0079] 《Separators for power storage devices》

[0080] The separator for a power storage device has a porous structure in which many very small pores are gathered to form dense interconnecting pores, so it exhibits high ion conductivity when impregnated with an electrolyte, has good withstand voltage characteristics, and has high physical strength. The separator for a power storage device may be a single-layer film or a laminated film.

[0081] The film thickness of the separator for the storage device is preferably 0.1 μm or more and 100 μm or less, more preferably 1 μm or more and 50 μm or less, and further preferably 3 μm or more and 25 μm or less. From the viewpoint of mechanical strength, the film thickness is preferably 0.1 μm or more, and from the viewpoint of high capacity of the battery, the film thickness is preferably 100 μm or less. The film thickness of the separator can be adjusted by controlling the die lip interval, the stretching ratio of the stretching process, etc.

[0082] The average pore size of the separator for a storage device is preferably from 10 nm to 100 nm, more preferably from 20 nm to 90 nm, further preferably from 30 nm to 80 nm, and particularly preferably from 40 nm to 80 nm from the viewpoint of ion conductivity and withstand voltage. The average pore size can be adjusted by controlling the composition ratio, the cooling rate of the extruded sheet, the stretching temperature, the stretching ratio, the heat setting temperature, the stretching ratio during heat setting, the relaxation rate during heat setting, or a combination thereof.

[0083] The average pore size can be measured by the gas-liquid method. Specifically, it is known that the fluid inside the capillary follows the Knudzen flow when the mean free flow of the fluid is larger than the pore size of the capillary, and follows the Poiseuille flow when the mean free flow of the fluid is smaller than the pore size of the capillary. Therefore, it is assumed that in the air permeability measurement of the separator, the flow of air follows the Knudzen flow, and in the water permeability measurement, the flow of water follows the Poiseuille flow.

[0084] At this time, the average pore size d (μm) and the tortuosity τ of the porous membrane a (dimensionless) from the air permeation rate constant R gas (m 3 / (m 2 ·second·Pa)), water permeation rate constant R liq (m 3 / (m 2 ·second·Pa)), air molecular velocity ν (m / second), water viscosity η (Pa·second), standard pressure P s (=101325 Pa), porosity ε (%), and film thickness L (μm) were calculated using the following formulas.

[0085] d=2ν×(R liq / R gas )×(16η / 3P s )×10 6

[0086] τ a =(d×(ε / 100)×ν / (3L×P s ×R gas )) 1 / 2

[0087] Here, R gas The air permeability (seconds) was calculated using the following formula.

[0088] R gas =0.0001 / (air permeability×(6.424×10 -4 )×(0.01276×101325))

[0089] In addition, R liq By water permeability (cm 3 / (cm 2 ·second·Pa) is calculated using the following formula.

[0090] R liq = Water permeability / 100

[0091] It should be noted that the water permeability was determined as follows. A separator pre-immersed in ethanol was installed in a stainless steel permeation tank with a diameter of 41 mm. The ethanol in the separator was washed with water, and water was passed through the separator at a pressure difference of about 50,000 Pa. The water permeability (cm 3 ) Calculate the amount of water permeable per unit time, unit pressure, and unit area, and use it as the water permeability.

[0092] In addition, ν is determined by the gas constant R (=8.314 J / (K·mol)), absolute temperature T (K), pi, and the average molecular weight of air M (=2.896×10 -2kg / mole) was calculated using the following formula.

[0093] ν=((8R×T) / (π×M)) 1 / 2

[0094] The porosity of the separator for the storage device is preferably 25% or more and 95% or less, more preferably 30% or more and 85% or less, further preferably 35% or more and 75% or less, and particularly preferably 40% or more and 65% or less. From the viewpoint of improving ion conductivity, the porosity is preferably 25% or more, and from the viewpoint of voltage resistance, the porosity is preferably 95% or less. The porosity of the separator can be adjusted by controlling the mixing ratio of the polyolefin resin composition and the plasticizer, the stretching temperature, the stretching ratio, the heat setting temperature, the stretching ratio during heat setting, the relaxation rate during heat setting, or a combination thereof.

[0095] The air permeability of the separator for power storage device is preferably 10 seconds / 100ml or more and 500 seconds / 100ml or less, more preferably 20 seconds / 100ml or more and 400 seconds / 100ml or less, further preferably 30 seconds / 100ml or more and 300 seconds / 100ml or less, and particularly preferably 40 seconds / 100ml or more and 200 seconds / 100ml or less. If the air permeability is 10 seconds / 100ml or more, there is a tendency to reduce self-discharge when used as a separator for power storage device, and if it is 500 seconds / 100ml or less, there is a tendency to obtain good charge and discharge characteristics, so it is preferred.

[0096] The puncture strength of the separator for the storage device is preferably 100 gf or more, more preferably 200 gf or more, further preferably 300 gf or more, preferably 600 gf or less, more preferably 500 gf or less, and further preferably 400 gf or less. Adjusting the puncture strength to 100 gf or more is preferred from the viewpoint of suppressing the film breakage caused by the active material that falls off during the electric field winding, and is also preferred from the viewpoint of reducing the possibility of short circuit due to the expansion and contraction of the electrode accompanying the charge and discharge. On the other hand, adjusting the puncture strength to 600 gf or less is preferred from the viewpoint of reducing the contraction caused by the relaxation of the orientation during heating.

[0097] The viscosity average molecular weight of the polyolefin resin contained in the separator for the storage device is preferably 200,000 or more and 5,000,000 or less, more preferably 300,000 or more and 3,000,000 or less, and further preferably 400,000 or more and 1,000,000 or less. If the viscosity average molecular weight is 200,000 or more, there is a tendency that the melt tension during melt forming increases, the formability becomes good, and high strength is formed by the mutual entanglement between the polyolefin resins. If the viscosity average molecular weight is 5,000,000 or less, it becomes easy to melt-mix uniformly, and there is a tendency that the formability of the sheet, especially the thickness stability, is excellent. Furthermore, when the separator is used as a separator for the storage device, if the viscosity average molecular weight of the separator is less than 1,000,000, there is a tendency that the pores are easily blocked when the temperature rises and a good fuse function is obtained, so it is preferred.

[0098] The whiteness of the separator for the power storage device is greater than 98.0 and less than 105, preferably greater than 98.5 and less than 104, and more preferably greater than 99 and less than 103. If the whiteness of the separator exceeds 98.0, the reliability and safety of the power storage device can be improved because the degradation of the polyolefin is less. If the whiteness of the separator is less than 105, it is preferred from a practical point of view because a separator with less degradation of the polyolefin can be effectively manufactured.

[0099] The whiteness is measured using a colorimeter "SC-T" (manufactured by Suga Test Instruments Co., Ltd.) with a 2° field of view without regular reflected light. When the thickness of the separator is 20 μm or less, the color of the back side of the separator to be measured may not be detected, and the whiteness of the separator may not be accurately measured. Therefore, the whiteness of the present invention is defined as the value obtained by folding the separator to make the total thickness of 20 μm or more when the thickness of the separator is 20 μm or less.

[0100] The withstand voltage of the separator for the storage device can be measured using a withstand voltage / insulation resistance tester (TOS9201, manufactured by Kikusui Electronics Co., Ltd.). Specifically, for example, the separator is sandwiched between smooth metal plates, the applied voltage is increased at a rate of 1 kV / second, and the voltage value for detecting a short circuit is measured (AC 60 Hz). When comparing the withstand voltage values ​​of separators of different thicknesses, if the thickness is standardized, the inherent withstand voltage values ​​can be compared. Therefore, in the embodiments described below, the withstand voltage values ​​converted to 20 μm are calculated to compare the separators. For the withstand voltage per 20 μm (kV / 20 μm), from the viewpoint of suppressing film breakage caused by active materials that fall off during the preparation of the winding body, it is preferably 1.3 kV / 20 μm or more, more preferably 1.4 kV / 20 μm or more, and further preferably 1.5 kV / 20 μm or more.

[0101] The reason why the degradation of the polyolefin contained in the separator for the storage device of the present embodiment is suppressed is not necessarily clear, and is not limited by the reasons based on the effects or principles described in this paragraph, but it is believed that the separator of the present embodiment uses a filler that does not induce the degradation of the polyolefin. As one of the methods for making microparticles, metal oxides such as silicon dioxide are known to hydrolyze SiCl4 at high temperature (combustion method). At this time, it is difficult to completely remove the hydrogen chloride as a by-product, so it is believed that the degradation of the polyolefin is promoted due to the residual acidic components. On the other hand, ionic compounds are mostly used as methods for making microparticles. Chemical synthesis methods such as coprecipitation methods are considered to be easier to reduce the amount of impurities and less likely to produce degradation of polyolefins caused by impurities than the method of crushing natural ores. It is speculated that by using ionic compounds with few impurities, the whiteness of the resulting separator can be increased to more than 98.0.

[0102] Furthermore, the separator for the storage device of the present embodiment preferably contains polyethylene with a viscosity average molecular weight of 600,000 or more from the viewpoint of improving whiteness. The reason for the improvement of whiteness when using the above polyethylene is not necessarily clear, and is not limited by the reasons based on the effects or principles described in this paragraph, but it is believed that if polyethylene with a viscosity average molecular weight of 600,000 or more is contained, as a result of the polyethylene being highly entangled in the ionic compound, the fibril portion constituting the porous layer is densified and the reflected light is uniformized, and as a result, there is a tendency for the whiteness of the separator to increase. That is, if the separator of the present embodiment contains a polyolefin resin and an ionic compound, especially polyethylene with a viscosity average molecular weight of 600,000 or more in the same layer, there is a tendency to obtain a separator with a whiteness exceeding 98.0, so it is preferred.

[0103] 《Method for manufacturing separator for power storage device》

[0104] An example of a method for producing a separator for a power storage device of the present invention is described, but the method is not necessarily limited to this example. The method for producing a separator may include the following steps:

[0105] (1) a step of melt-kneading a polyolefin resin, an ionic compound and a plasticizer to obtain a melt;

[0106] (2) A step of transferring and forming the melt into a sheet and then cooling and solidifying the sheet;

[0107] (3) a step of stretching the sheet-like molded body in at least one uniaxial direction at an area ratio of 20 times or more and less than 200 times; and

[0108] (4) A step of extracting the plasticizer from the sheet-like molded product after the stretching step.

[0109] In the step (1), a polyolefin resin, an ionic compound and a plasticizer are melt-kneaded. Examples of the melt-kneading method include a method in which a polyolefin resin, an ionic compound and other additives as required are introduced into a resin kneading device such as an extruder, a kneader, a Labo Plasto Mill, a kneading roll, a Banbury mixer, etc., and a plasticizer is introduced at an arbitrary ratio while heating and melting the resin components to perform kneading.

[0110] There are no particular limitations on the plasticizer, but it is preferred to use a non-volatile solvent that can form a uniform solution above the melting point of the polyolefin resin. Specific examples of such non-volatile solvents include hydrocarbons such as liquid paraffin and paraffin wax; esters such as dioctyl phthalate and dibutyl phthalate; higher alcohols such as oleyl alcohol and stearyl alcohol, etc. It should be noted that these plasticizers can be recovered and reused by operations such as distillation after extraction. Furthermore, it is preferred that the polyolefin resin, ionic compounds, other additives and plasticizers are pre-mixed in a specified ratio using a Henschel mixer or the like before being put into the resin mixing device. It is more preferred that only a part of the plasticizer is put into the pre-mixing, and the remaining plasticizer is appropriately heated and mixed while being fed sideways to the resin mixing device. By using such a kneading method, the dispersibility of the plasticizer is improved, and in the subsequent step, when a sheet-like molded product of the melt-kneaded product of the resin composition and the plasticizer is stretched, it tends to be possible to stretch at a high ratio without film breakage.

[0111] Among plasticizers, liquid paraffin is preferred because it has high compatibility with polyethylene or polypropylene when the polyolefin resin is these and does not easily cause interfacial peeling of the resin and the plasticizer even when the melt-kneaded product is stretched, and uniform stretching tends to be easy.

[0112] The ratio of polyolefin resin, ionic compound and plasticizer is not particularly limited if it is within the range that they can be uniformly melt-kneaded and formed into a sheet. For example, the mass fraction of the plasticizer in the composition comprising polyolefin resin, ionic compound and plasticizer is preferably 10 to 90 mass%, more preferably 20 to 80 mass%. If the mass fraction of the plasticizer is 90 mass% or less, there is a tendency that the melt tension during melt molding is sufficient for improving the formability. On the other hand, if the mass fraction of the plasticizer is 10 mass% or more, even if the mixture of the polyolefin resin composition and the plasticizer is stretched at a high ratio, the polyolefin molecular chain will not break, and a uniform and fine pore structure is easily formed, and the strength is also easily increased.

[0113] In the process of (2), the molten kneaded product is formed into a sheet. As a method for manufacturing a sheet-like molded body, for example, a method in which the molten kneaded product is extruded into a sheet by a T-die, etc., and is cooled to a temperature sufficiently lower than the crystallization temperature of the resin component by contact with a heat conductor to solidify. As the heat conductor used in cooling and solidification, metal, water, air or plasticizer can be listed. Among them, metal rollers are preferably used because of their high efficiency of heat conduction. In addition, when the extruded kneaded product is brought into contact with a metal roller, it is more preferred to sandwich the rollers because the efficiency of heat conduction is further increased, the film strength is increased due to sheet orientation, and the surface smoothness of the sheet is also improved. The die lip spacing when the molten kneaded product is extruded into a sheet from a T-die is preferably 200 μm or more and 3000 μm or less, more preferably 500 μm or more and 2500 μm or less. If the die lip interval is 200 μm or more, die burns are reduced, and the influence of streaks and defects on film quality is less, and the risk of film breakage can be reduced in the subsequent stretching process. On the other hand, if the die lip interval is 3000 μm or less, the cooling speed is fast, uneven cooling is prevented, and the thickness stability of the sheet can be maintained.

[0114] In addition, the sheet-like formed body can also be calendered. Calendering can be implemented, for example, by a pressurization method using a double-belt press or the like. By implementing calendering, the orientation of the surface layer can be particularly increased. The calendering surface ratio is preferably more than 1 times and less than 3 times, more preferably more than 1 times and less than 2 times. If the calendering ratio exceeds 1 times, there is a tendency that the surface orientation increases and the membrane strength of the separator finally obtained increases. On the other hand, if the calendering ratio is less than 3 times, there is a tendency that the orientation difference between the surface layer and the center is small, and a uniform porous structure can be formed in the thickness direction of the membrane.

[0115] In the step (3), the sheet-like molded body is stretched. The stretching may be performed after the plasticizer is extracted from the sheet-like molded body. Furthermore, the stretching may be performed before or after the plasticizer is extracted from the sheet-like molded body.

[0116] As a stretching treatment, uniaxial stretching or biaxial stretching can be used appropriately, but from the viewpoint of improving the strength of the obtained separator, biaxial stretching is preferably used. If the sheet-like formed body is stretched at a high ratio in a biaxial direction, the molecules are oriented in the plane direction, and the separator finally obtained is not easy to break and has a high puncture strength. As a stretching method, methods such as simultaneous biaxial stretching, sequential biaxial stretching, multi-stage stretching, and many times of stretching can be listed. From the viewpoint of improving puncture strength, uniformity of stretching, and fuse characteristics, it is preferably simultaneous biaxial stretching. In addition, from the viewpoint of the ease of controlling the plane orientation, it is preferably sequential biaxial stretching.

[0117] Simultaneous biaxial stretching refers to a stretching method in which stretching in MD (machine direction in which the separator is continuously formed) and stretching in TD (direction of the separator crossing MD at an angle of 90°) are simultaneously performed, and the stretching ratio in each direction may be different. Sequential biaxial stretching refers to a stretching method in which stretching in MD and TD is performed independently, and when stretching in MD or TD, the other direction is formed into an unrestricted state or a state fixed to a fixed length.

[0118] The stretching ratio is preferably in the range of 20 times or more and 200 times or less, more preferably in the range of 25 times or more and 150 times or less, by surface ratio. The stretching ratio in each axial direction is preferably in the range of 4 times or more and 15 times or less for MD, in the range of 4 times or more and 15 times or less for TD, more preferably in the range of 5 times or more and 12 times or less for MD, in the range of 5 times or more and 12 times or less for TD. If the total area ratio is more than 25 times, there is a tendency to give sufficient strength to the obtained separator. On the other hand, if the total area ratio is less than 200 times, the separator in the stretching process is prevented from breaking, and there is a tendency to obtain high productivity.

[0119] In the step (4), the plasticizer is removed from the sheet-like formed body to form a separator. As a method for removing the plasticizer, there can be cited a method in which, for example, the sheet-like formed body is impregnated with an extraction solvent to extract the plasticizer, and then the plasticizer is fully dried. The method for extracting the plasticizer may be either intermittent or continuous. In order to suppress the shrinkage of the separator, it is preferred to limit the end of the sheet-like formed body in a series of impregnation and drying steps. In addition, the amount of plasticizer residue in the separator is preferably adjusted to less than 1% by mass relative to the mass of the entire separator.

[0120] As the extraction solvent used when extracting the plasticizer, it is preferred to use a solvent that is a poor solvent for the polyolefin resin and a good solvent for the plasticizer, and has a boiling point lower than the melting point of the polyolefin resin. Examples of such extraction solvents include hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as dichloromethane and 1,1,1-trichloroethane; non-chlorine halogenated solvents such as hydrofluoroethers and hydrofluorocarbons; alcohols such as ethanol and isopropanol; ethers such as diethyl ether and tetrahydrofuran; and ketones such as acetone and methyl ethyl ketone. It should be noted that these extraction solvents can be recovered and reused by operations such as distillation.

[0121] In order to suppress the shrinkage of the separator, a heat treatment may be performed for the purpose of heat setting after the stretching process or after the separator is formed. In addition, the separator may be subjected to post-treatment such as hydrophilization treatment using a surfactant or the like, cross-linking treatment using ionizing radiation or the like.

[0122] For the separator, from the viewpoint of suppressing shrinkage, it is preferred to implement heat treatment with heat setting as the purpose. As the method of heat treatment, a stretching operation performed with a specified temperature atmosphere and a specified stretching rate for the purpose of adjusting physical properties, and / or a relaxation operation performed with a specified temperature atmosphere and a specified relaxation rate for the purpose of reducing tensile stress can be listed. It is also possible to perform a relaxation operation after the stretching operation. These heat treatments can be performed using a tenter or a roller stretching machine.

[0123] The stretching operation is preferably performed by stretching the MD and / or TD of the film by more than 1.1 times, more preferably more than 1.2 times, which is preferred from the viewpoint of obtaining a separator with further high strength and high porosity. The relaxation operation is a shrinking operation on the MD and / or TD of the film. The relaxation rate refers to the value obtained by dividing the size of the film after the relaxation operation by the size of the film before the relaxation operation. It should be noted that when both MD and TD are relaxed, the relaxation rate is the value obtained by multiplying the relaxation rate of MD and the relaxation rate of TD. The relaxation rate is preferably less than 1.0, more preferably less than 0.97, and further preferably less than 0.95. The relaxation rate is preferably more than 0.5 from the viewpoint of film quality. The relaxation operation can be performed in both MD and TD directions, but it can also be performed in only one direction of MD and TD.

[0124] The stretching and relaxation operation after the plasticizer extraction is preferably performed on TD. The temperature of the stretching and relaxation operation is preferably Tm-20°C or more and Tm+20°C or less, and more preferably Tm-10°C or more and Tm+10°C or less, compared to the melting point (hereinafter also referred to as "Tm") of the polyolefin resin. If the temperature of the stretching and relaxation operation is within the above range, it is preferred from the viewpoint of balancing the reduction of heat shrinkage and porosity.

[0125] If the separator is made by a "wet method" in which the porous material is extracted by a plasticizer, the size, shape, and position distribution of the pores are easily equalized, and as a result, the reflected light of the separator is uniformized, and there is a tendency for the whiteness of the separator to increase. Therefore, from the viewpoint of increasing the whiteness of the separator to more than 98.0, the porous material is preferably extracted by a plasticizer.

[0126] The separator for the storage device of this embodiment fully functions as a separator for the storage device even when used alone, but can also be coated with inorganic materials and / or organic materials to form a laminated film as needed. The separator for the storage device of this embodiment has high heat resistance and little degradation of polyolefin, so it can improve the reliability and safety of the storage device.

[0127] 《Electricity Storage Device》

[0128] The power storage device of the present embodiment is equipped with a positive electrode, a negative electrode, and a separator for the power storage device of the present embodiment. As the power storage device, specifically, a lithium secondary battery, a lithium ion secondary battery, a sodium secondary battery, a sodium ion secondary battery, a magnesium secondary battery, a magnesium ion secondary battery, a calcium secondary battery, a calcium ion secondary battery, an aluminum secondary battery, an aluminum ion secondary battery, a nickel-hydrogen battery, a nickel-cadmium battery, a double-layer capacitor, a lithium ion capacitor, a redox flow battery, a lithium-sulfur battery, a lithium-air battery, a zinc-air battery, etc. can be listed. Among the above, from the viewpoint of practicality, preferably a lithium secondary battery, a lithium ion secondary battery, a nickel-hydrogen battery, or a lithium ion capacitor, more preferably a lithium ion secondary battery.

[0129] The storage device of the present embodiment can be manufactured, for example, as follows: the positive electrode and the negative electrode are overlapped with each other via a separator, and wound as needed to form a stacked electrode body or a wound electrode body, which is then loaded into an outer casing, the positive and negative electrodes are connected to the positive and negative terminals of the outer casing by means of a conductor, etc., and a non-aqueous electrolyte containing a non-aqueous solvent such as a chain or cyclic carbonate and an electrolyte such as a lithium salt is injected into the outer casing, and then the outer casing is sealed to manufacture the storage device of the present embodiment.

[0130] The outer shell of the power storage device is not particularly limited, and a metal can container or a laminated container formed by a metal foil laminate film can be suitably used. It should be noted that the shape of the power storage device is not particularly limited, and if an example is given, a cylindrical, square, coin-shaped, flat, sheet-shaped, etc. is adopted.

[0131] "positive electrode"

[0132] The positive electrode is prepared as follows: a conductive aid such as acetylene black and a binder such as polyvinylidene fluoride are added to the positive electrode active material in an appropriate amount to prepare a positive electrode mixture, which is applied to a current collector such as aluminum foil and dried and then pressed to bond a positive electrode mixture layer to the current collector to prepare the positive electrode. However, the method for preparing the positive electrode is not limited to the method exemplified above.

[0133] The positive electrode active material is not particularly limited, but is preferably selected from the general formula LiNi x Co y Ma 1-x-y O2 [wherein, Ma represents one or more selected from the group consisting of Mn and Al, 0≤x≤1, 0≤y≤1, and x+y≤1] a layered oxide positive electrode active material; general formula LiMn 2-x Mb xO4 [wherein, Mb represents one or more selected from the group consisting of transition metals, and 0.2≤x≤0.7] as a spinel oxide positive electrode active material; as a composite oxide of Li2McO3 and LiMdO2 [wherein, Mc and Md each independently represent one or more selected from the group consisting of transition metals], a Li-excess layered oxide positive electrode active material represented by the general formula zLi2McO3-(1-z)LiMdO2 [wherein, Mc and Md each independently represent one or more selected from the group consisting of transition metals, and 0.05≤z≤0.95]; LiMe 1-x Fe x Olivine-type positive electrode active material represented by PO4 [wherein Me represents one or more selected from the group consisting of Mn and Co, and 0≤x≤1]; and one or more positive electrode active materials in the group consisting of Li2MfPO4F [wherein Mf represents one or more selected from the group consisting of transition metals], etc.

[0134] General formula LiNi x Co y Ma 1-x-y The layered oxide positive electrode active material represented by O2 [wherein Ma represents one or more selected from the group consisting of Mn and Al, 0≤x≤1, 0≤y≤1, and x+y≤1] preferably has LiNi x Co y Mn 1-x-y O2[where 0≤x≤1, 0≤y≤1, and x+y≤1] or LiNi x Co y Al 1-x-y O2 [wherein, 0.7≤x≤1, 0≤y≤0.3, and x+y≤1] is a composition. More preferred compositions include LiCoO2, LiNi x Co y Mn 1-x-y O2[where 0.3≤x≤1, 0≤y≤0.4, and x+y≤1], and LiNi 0.85 Co 0.1 Al 0.05 O2.

[0135] "negative electrode"

[0136] The negative electrode is prepared as follows: a thickener such as carboxymethyl cellulose and a binder such as styrene butadiene rubber are added to the negative electrode active material in an appropriate amount to prepare a negative electrode mixture, which is applied to a current collector such as copper foil and dried and then pressed to adhere a negative electrode mixture layer to the current collector to prepare the negative electrode. However, the method for preparing the negative electrode is not limited to the method exemplified above.

[0137] In the present embodiment, the negative electrode active material that can be used for the negative electrode is not particularly limited, and for example, alloy compounds of Al, Si, Sn, etc.; metal oxides such as CuO and CoO; lithium-containing compounds such as lithium titanate; and carbon materials can be used. From the viewpoint of improving the energy density of the storage device, a carbon material that can absorb and release lithium ions at a relatively low potential is preferred. Such carbon materials are not particularly limited, and examples thereof include hard carbon, soft carbon, artificial graphite, natural graphite, pyrolytic carbon, coke, glassy carbon, calcined bodies of organic polymer compounds, calcined bodies of organic natural products, carbon fibers, mesophase carbon microbeads, carbon black, and the like.

[0138] When a carbon material is used as the negative electrode active material, the interlayer distance d of the (002) plane of the carbon material is 002 It is preferably 0.37 nm or less, more preferably 0.35 nm or less, and further preferably 0.34 nm or less. 002 The lower limit is not particularly limited, but theoretically it is about 0.335 nm. In addition, the size of the crystallite in the c-axis direction of the carbon material is preferably greater than 3 nm, more preferably greater than 8 nm, and further preferably greater than 25 nm. There is no particular limit on the upper limit of the size of the crystallite, but it is generally around 200 nm. The average particle size of the carbon material is preferably greater than 3 μm and less than 15 μm, more preferably greater than 5 μm and less than 13 μm. In addition, the purity of the carbon material is preferably greater than 99.9%.

[0139] The power storage device of this embodiment has high safety and excellent productivity, and therefore can be widely used as a power source for various devices including batteries for consumer devices such as smartphones, in addition to being used as a vehicle-mounted battery.

[0140] Example

[0141] The present invention will be described in detail below using examples, but the present invention is not limited to the following examples unless the gist of the invention is exceeded. The analysis methods and evaluation methods used in the examples and comparative examples are as follows.

[0142] (1) Film thickness (μm)

[0143] The film thickness of the sample was measured at room temperature of 23° C. using a micro thickness gauge (manufactured by Toyo Seiki Co., Ltd., type KBM).

[0144] (2) Porosity (%)

[0145] Cut a 10 cm x 10 cm square sample from the separator and calculate its volume (cm 3 ) and mass (g), and the film density (g / cm 3 )The porosity was calculated using the following formula.

[0146] Porosity (%) = (volume - mass / membrane density) / volume × 100

[0147] In addition, as a film density, the value calculated from each density and the mixing ratio of the polyolefin resin and the ionic compound used was used.

[0148] (3) Air permeability (seconds / 100ml)

[0149] The air permeability of the sample was measured using a Gurley air permeometer (manufactured by Toyo Seiki Co., Ltd.) in accordance with JIS P-8117.

[0150] (4)Puncture strength (gf)

[0151] The partition was fixed using a portable compression tester "KES-G5" (manufactured by KATO TECH CO., LTD.) using a sample holder with an opening diameter of 11.3 mm. A puncture test was performed on the central portion of the fixed partition under the conditions of a curvature radius of 0.5 mm at the tip of the needle and a puncture speed of 2 mm / sec in an atmosphere of 25°C, and the puncture strength (gf) was measured as the maximum puncture load.

[0152] (5) Whiteness

[0153] The whiteness of the separator was measured using a colorimeter "SC-T" (manufactured by Suga Test Instruments Co., Ltd.) When the thickness of the separator was less than 20 μm, the separator was folded so that the total thickness was 20 μm or more, and the whiteness was measured under the condition of 2° field of view without regular reflection light.

[0154] (6) Withstand voltage (kV / 20μm)

[0155] Using a withstand voltage / insulation resistance tester "TOS9201" (manufactured by Kikusui Electronics Co., Ltd.), a separator was sandwiched between smooth metal plates, and the applied voltage was increased at a rate of 1 kV / second to measure the voltage value (AC 60 Hz) at which a short circuit was detected. The obtained voltage value was converted into a withstand voltage value per 20 μm (kV / 20 μm) using the following formula.

[0156] Withstand voltage (kV / 20μm) = voltage measurement value (kV) × 20 ÷ film thickness (μm)

[0157] (7) Welding test (mm) 2 )

[0158] A soldering iron with a diameter of 1 mm at the front end was set perpendicularly to the frame-fixed separator. The temperature of the soldering iron was raised to 400°C. After the temperature stabilized, the soldering iron was lowered at a speed of 10 mm / second, pierced the separator for 3 seconds, and then raised. The area of ​​the hole in the separator was observed with an optical microscope, and the area was calculated by image processing.

[0159] (8) Tests using lithium-ion secondary batteries

[0160] 《Production of positive electrode sheet》

[0161] LiNi as the positive electrode active material 1 / 3 Mn 1 / 3 Co 1 / 3 O2 (manufactured by Nippon Chemical Industry Co., Ltd.), acetylene black powder (manufactured by Denki Kagaku Kogyo Co., Ltd.) as a conductive aid, and polyvinylidene fluoride solution (manufactured by KUREHA CORPORATION) as a binder were mixed at a solid content mass ratio of 90:6:4, and N-methyl-2-pyrrolidone was added as a dispersing solvent to make the solid content 40% by mass, and further mixed to prepare a slurry solution. The slurry solution was applied to both sides of an aluminum foil with a thickness of 20 μm as a current collector, the solvent was dried and removed, and then the coated aluminum foil was rolled by roller pressure to obtain a positive electrode sheet.

[0162] 《Production of negative electrode sheet》

[0163] Graphite powder (manufactured by Osaka Gas Chemicals Co., Ltd.) as a negative electrode active material, styrene butadiene rubber and carboxymethyl cellulose aqueous solution as a binder were mixed at a solid content mass ratio of 100:1.5:1.8, and water was added as a dispersion solvent to make the solid content 45% by mass, and further mixed to produce a slurry solution. The slurry solution was applied to both sides of a copper foil with a thickness of 18 μm as a current collector, the solvent was dried and removed, and then the coated copper foil was rolled using roller pressure to obtain a negative electrode sheet.

[0164] 《Manufacturing of non-aqueous electrolyte》

[0165] A solution containing 1 mol / L of LiPF6 in a mixed solvent of ethylene carbonate and ethyl methyl carbonate as a non-aqueous solvent in a volume ratio of 1:2 was prepared.

[0166] 《Manufacturing of lithium-ion secondary batteries》

[0167] The positive electrode sheet and the negative electrode sheet prepared as described above are overlapped on both sides of the separator obtained in the embodiments and comparative examples described later to obtain a laminate. The obtained laminate is inserted into a bag (outer shell) formed by an aluminum laminate film with both sides of an aluminum foil (thickness 40 μm) covered with a resin layer while protruding the positive and negative terminals. Then, the non-aqueous electrolyte prepared as described above is injected into the bag, and the bag is vacuum-sealed to prepare a small pouch lithium-ion secondary battery.

[0168] 《Initial charge and discharge of lithium-ion secondary batteries》

[0169] The pouch-type lithium-ion secondary battery is placed in a thermostatic bath "PLM-73S" (manufactured by Futaba Science Co., Ltd.) set at 25°C, and connected to a charge and discharge device "ACD-01" (manufactured by ASKA ELECTRONIC CO., LTD.). Next, the secondary battery is charged at a constant current of 0.1C until a voltage of 4.2V is reached, charged at a constant voltage of 4.2V for 1 hour, and then discharged at a constant current of 0.1C to 3.0V. Such a charge and discharge cycle is repeated 3 times. Then, the battery is charged at a constant current of 0.1C until a voltage of 4.2V is reached, so that the lithium-ion secondary battery is in a fully charged state. It should be noted that 1C represents the current value when the total capacity of the battery is discharged in 1 hour, and 0.1C represents a current value of 1 / 10 thereof.

[0170] 《20C discharge test of lithium-ion secondary batteries》

[0171] The pouch-type lithium-ion secondary battery after the initial charge and discharge is placed in a thermostatic chamber "PLM-73S" (manufactured by Futaba Science Co., Ltd.) set at 25°C, and connected to a charge and discharge device "ACD-01" (manufactured by ASKA ELECTRONIC CO., LTD.). Next, the secondary battery is charged at a constant current of 1 / 3C until a voltage of 4.2V is reached, then charged at a constant voltage of 4.2V for 1 hour, and discharged at a constant current of 1C to 3.0V. Then, the battery is charged at a constant current of 1 / 3C until a voltage of 4.2V is reached, then charged at a constant voltage of 4.2V for 1 hour, and discharged at a constant current of 20C to 3.0V. From the results of the above series of charge and discharge, the 20C capacity retention rate (%) is calculated using the following formula.

[0172] 20C capacity retention rate (%) = 20C discharge capacity / 1C discharge capacity × 100

[0173] 《Cycle test of lithium-ion secondary batteries》

[0174] The pouch-type lithium-ion secondary battery after the 20C discharge test was placed in a thermostatic chamber "PLM-73S" (manufactured by Futaba Science Co., Ltd.) set at 50°C, and connected to a charge and discharge device "ACD-01" (manufactured by ASKA ELECTRONIC CO., LTD.). Next, the secondary battery was charged at a constant current of 1C until a voltage of 4.2V was reached, charged at a constant voltage of 4.2V for 1 hour, and discharged at a constant current of 1C to 3.0V. The above series of charge and discharge was regarded as one cycle, and it was cycled 100 times, and the capacity retention rate (%) after 100 cycles was determined. It should be noted that the capacity retention rate (%) after 100 cycles is calculated using the following formula.

[0175] Capacity retention rate after 100 cycles (%) = discharge capacity at the 100th cycle / discharge capacity at the 1st cycle × 100

[0176] The materials used in Examples and Comparative Examples are as follows.

[0177] (1) Polyolefin resin

[0178] Polyethylene A (UH650, manufactured by Asahi Kasei Corporation) with a viscosity average molecular weight of 700,000 and a melting point of 135°C

[0179] Polyethylene B (7000FP, manufactured by Prime Polymer Co., Ltd.) with a viscosity average molecular weight of 260,000 and a melting point of 131°C

[0180] Polyethylene C (UH850, manufactured by Asahi Kasei Corporation) with a viscosity average molecular weight of 2 million and a melting point of 135°C

[0181] (2) Ionic compounds and metal oxides

[0182] Barium sulfate with an average particle size of 10 nm (coprecipitation method)

[0183] Barium sulfate with an average particle size of 50 nm (coprecipitation method)

[0184] Barium sulfate with an average particle size of 660nm (ore crushing method)

[0185] Sodium phosphate with an average particle size of 500nm (coprecipitation method)

[0186] Aluminum sulfate with an average particle size of 800nm ​​(coprecipitation method)

[0187] Lithium fluoride with an average particle size of 30nm

[0188] Silicon dioxide with an average particle size of 16nm (combustion method)

[0189] Alumina with an average particle size of 10 nm (combustion method)

[0190] Boehmite with an average particle size of 800nm ​​(hydrothermal synthesis method)

[0191] Potassium titanate with an average particle size of 400nm

[0192] (3) Plasticizer

[0193] Liquid paraffin with a kinematic viscosity of 70.6 cSt at 40°C

[0194] (4) Antioxidants

[0195] Tetrakis-[methylene-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane

[0196] [Example 1]

[0197] Polyethylene A (85 parts by mass), barium sulfate (15 parts by mass) having an average particle size of 50 nm, and an antioxidant (0.85 parts by mass) were dry-blended using a Henschel mixer to obtain a mixed raw material.

[0198] The mixed raw material is supplied to the twin-screw extruder by a feeder under a nitrogen atmosphere. In addition, liquid paraffin is injected into the extruder barrel by a plunger pump. The operating conditions of the feeder and the pump are adjusted so that the ratio of liquid paraffin in the entire extruded mixture is 66 parts by mass and the ratio of polymer and ionic compound is 34 parts by mass. Then, they are melt-kneaded while being heated to 200° C. in the twin-screw extruder, and the obtained molten kneaded product is extruded through a T-die onto a cooling roller whose surface temperature is controlled to 90° C., and the extrudate is brought into contact with the cooling roller, formed, cooled and solidified, thereby obtaining a sheet-like formed product.

[0199] The sheet-like formed product was stretched to a ratio of 7×6.4 times at a temperature of 122°C using a simultaneous biaxial stretching machine, and the stretched product was immersed in dichloromethane to extract and remove the liquid paraffin, and then dried. The obtained stretched sheet was then stretched 1.8 times in the width direction at a temperature of 134°C using a uniaxial stretching machine, and the stretched sheet was relaxed by about 20% in the width direction to obtain a separator. The evaluation results of the obtained separator are shown in Table 1.

[0200] [Example 2]

[0201] Polyethylene A (70 parts by mass), barium sulfate (30 parts by mass) having an average particle size of 50 nm, and an antioxidant (0.7 parts by mass) were dry-mixed using a Henschel mixer to obtain a mixed raw material, and a separator was prepared in the same manner as in Example 1 except that the mixed raw material was used instead of the mixed raw material in Example 1. The evaluation results of the obtained separator are shown in Table 1.

[0202] [Example 3]

[0203] Polyethylene A (40 parts by mass), barium sulfate (60 parts by mass) having an average particle size of 50 nm, and an antioxidant (0.4 parts by mass) were dry-mixed using a Henschel mixer to obtain a mixed raw material, and the mixed raw material was used instead of the mixed raw material of Example 1. A separator was produced in the same manner as in Example 1. The evaluation results of the obtained separator are shown in Table 1.

[0204] [Example 4]

[0205] Polyethylene A (20 parts by mass), barium sulfate (80 parts by mass) having an average particle size of 50 nm, and an antioxidant (0.2 parts by mass) were dry-mixed using a Henschel mixer to obtain a mixed raw material, and the mixed raw material was used instead of the mixed raw material of Example 1. A separator was produced in the same manner as in Example 1. The evaluation results of the obtained separator are shown in Table 1.

[0206] [Example 5]

[0207] A separator was produced in the same manner as in Example 1 except that barium sulfate having an average particle size of 10 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 1. Table 1 shows the evaluation results of the obtained separator.

[0208] [Example 6]

[0209] A separator was produced in the same manner as in Example 2 except that barium sulfate having an average particle size of 10 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 2. Table 1 shows the evaluation results of the obtained separator.

[0210] [Example 7]

[0211] A separator was produced in the same manner as in Example 3 except that barium sulfate having an average particle size of 10 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 3. Table 1 shows the evaluation results of the obtained separator.

[0212] [Example 8]

[0213] A separator was produced in the same manner as in Example 4 except that barium sulfate having an average particle size of 10 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 4. Table 1 shows the evaluation results of the obtained separator.

[0214] [Example 9]

[0215] A separator was produced in the same manner as in Example 4 except that barium sulfate having an average particle size of 660 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 4. Table 1 shows the evaluation results of the obtained separator.

[0216] [Example 10]

[0217] A separator was produced in the same manner as in Example 1 except that polyethylene B was used instead of polyethylene A in Example 1. Table 1 shows the evaluation results of the obtained separator.

[0218] [Example 11]

[0219] A separator was produced in the same manner as in Example 1 except that sodium phosphate having an average particle size of 500 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 1. Table 1 shows the evaluation results of the obtained separator.

[0220] [Example 12]

[0221] A separator was produced in the same manner as in Example 2 except that sodium phosphate having an average particle size of 500 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 2. Table 2 shows the evaluation results of the obtained separator.

[0222] [Example 13]

[0223] The separator was produced in the same manner as in Example 3 except that sodium phosphate having an average particle size of 500 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 3. Table 2 shows the evaluation results of the obtained separator.

[0224] [Example 14]

[0225] A separator was produced in the same manner as in Example 4 except that sodium phosphate having an average particle size of 500 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 4. Table 2 shows the evaluation results of the obtained separator.

[0226] [Example 15]

[0227] Polyethylene C (5 parts by mass), sodium phosphate (95 parts by mass) having an average particle size of 500 nm, and an antioxidant (0.05 parts by mass) were dry-mixed using a Henschel mixer to obtain a mixed raw material, and the mixed raw material was used instead of the mixed raw material of Example 1. A separator was produced in the same manner as in Example 1. The evaluation results of the obtained separator are shown in Table 2.

[0228] [Example 16]

[0229] The separator was produced in the same manner as in Example 1 except that aluminum sulfate having an average particle size of 800 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 1. Table 2 shows the evaluation results of the obtained separator.

[0230] [Example 17]

[0231] A separator was produced in the same manner as in Example 2 except that aluminum sulfate having an average particle size of 800 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 2. Table 2 shows the evaluation results of the obtained separator.

[0232] [Example 18]

[0233] The separator was produced in the same manner as in Example 3 except that aluminum sulfate having an average particle size of 800 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 3. Table 2 shows the evaluation results of the obtained separator.

[0234] [Example 19]

[0235] The separator was produced in the same manner as in Example 4 except that aluminum sulfate having an average particle size of 800 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 4. Table 2 shows the evaluation results of the obtained separator.

[0236] [Example 20]

[0237] A separator was produced in the same manner as in Example 15 except that aluminum sulfate having an average particle size of 800 nm was used instead of the sodium phosphate having an average particle size of 500 nm in Example 15. Table 2 shows the evaluation results of the obtained separator.

[0238] [Example 21]

[0239] The separator was produced in the same manner as in Example 1 except that lithium fluoride having an average particle size of 30 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 1. Table 2 shows the evaluation results of the obtained separator.

[0240] [Example 22]

[0241] The separator was produced in the same manner as in Example 2 except that lithium fluoride having an average particle size of 30 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 2. Table 2 shows the evaluation results of the obtained separator.

[0242] [Example 23]

[0243] The separator was produced in the same manner as in Example 3 except that lithium fluoride having an average particle size of 30 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 3. Table 2 shows the evaluation results of the obtained separator.

[0244] [Example 24]

[0245] The separator was produced in the same manner as in Example 4 except that lithium fluoride having an average particle size of 30 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 4. Table 2 shows the evaluation results of the obtained separator.

[0246] [Example 25]

[0247] A separator was produced in the same manner as in Example 15 except that lithium fluoride having an average particle size of 30 nm was used instead of the sodium phosphate having an average particle size of 500 nm in Example 15. Table 2 shows the evaluation results of the obtained separator.

[0248] [Example 26]

[0249] Polyethylene C (14 parts by mass), barium sulfate (86 parts by mass) having an average particle size of 50 nm, and an antioxidant (0.14 parts by mass) were dry-mixed using a Henschel mixer to obtain a mixed raw material, and the mixed raw material was used instead of the mixed raw material of Example 1. A separator was produced in the same manner as in Example 1. The evaluation results of the obtained separator are shown in Table 2.

[0250] [Example 27]

[0251] Polyethylene C (10 parts by mass), barium sulfate (90 parts by mass) having an average particle size of 50 nm, and an antioxidant (0.1 parts by mass) were dry-mixed using a Henschel mixer to obtain a mixed raw material, and the mixed raw material was used instead of the mixed raw material of Example 1. A separator was produced in the same manner as in Example 1. The evaluation results of the obtained separator are shown in Table 2.

[0252] [Example 28]

[0253] A separator was produced in the same manner as in Example 15 except that barium sulfate having an average particle size of 50 nm was used instead of the sodium phosphate having an average particle size of 500 nm in Example 15. Table 2 shows the evaluation results of the obtained separator.

[0254] [Example 29]

[0255] Polyethylene C (1 part by mass), barium sulfate (99 parts by mass) having an average particle size of 50 nm, and an antioxidant (0.01 parts by mass) were dry-mixed using a Henschel mixer to obtain a mixed raw material, and the mixed raw material was used instead of the mixed raw material of Example 1. A separator was produced in the same manner as in Example 1. The evaluation results of the obtained separator are shown in Table 2.

[0256] [Comparative Example 1]

[0257] A separator was prepared in the same manner as in Example 1 except that a mixture raw material obtained by dry-blending polyethylene A (100 parts by mass) and an antioxidant (1 part by mass) was used instead of the mixture raw material in Example 1. The evaluation results of the obtained separator are shown in Table 1.

[0258] [Comparative Example 2]

[0259] Polyethylene B (50 parts by weight), barium sulfate (50 parts by weight) with an average particle size of 660 nm and an antioxidant (0.5 parts by weight) were dry-mixed using a Henschel mixer to obtain a mixture raw material, which was then fed into a twin-screw mixer and melt-mixed while heated to 180°C. The resulting melt-mixed material was hot-pressed at 180°C to obtain an original roll sheet. The original roll sheet was then subjected to simultaneous biaxial stretching at a ratio of 2x2x at 135°C. It was then subjected to simultaneous biaxial stretching at a ratio of 3x3x at 125°C. The evaluation results of the resulting separator are shown in Table 1.

[0260] [Comparative Example 3]

[0261] A separator was produced in the same manner as in Example 3 except that silicon dioxide having an average particle size of 16 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 3. Table 1 shows the evaluation results of the obtained separator.

[0262] [Comparative Example 4]

[0263] A separator was produced in the same manner as in Example 3 except that aluminum oxide having an average particle size of 10 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 3. Table 1 shows the evaluation results of the obtained separator.

[0264] [Comparative Example 5]

[0265] A separator was produced in the same manner as in Example 3 except that boehmite having an average particle size of 800 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 3. Table 2 shows the evaluation results of the obtained separator.

[0266] [Comparative Example 6]

[0267] A separator was produced in the same manner as in Example 3 except that potassium titanate (K2O·8TiO2) having an average particle size of 400 nm was used instead of barium sulfate having an average particle size of 50 nm in Example 3. Table 2 shows the evaluation results of the obtained separator.

[0268] [Table 1]

[0269]

[0270] [Table 2]

[0271]

[0272] As can be seen from Tables 1 and 2, Examples 1 to 29 have smaller pore areas in the welding test and better heat resistance than Comparative Example 1 which does not contain an ionic compound. Furthermore, Examples 1 to 29 have significantly higher 20C discharge capacities and the same or higher capacity retention rates after 100 cycles than Comparative Example 1. Therefore, the separator of this embodiment improves the safety, output characteristics, and durability of the power storage device.

[0273] Next, it can be seen that, compared with Comparative Example 2 in which a separator is made by a dry porous method without using a plasticizer, Examples 1 to 29 have significantly higher 20C discharge capacity and the same or higher capacity retention rate after 100 cycles. Furthermore, compared with Comparative Example 2, the separators of Examples 1 to 29 have higher whiteness and excellent voltage resistance. Therefore, it can be seen that the separator of this embodiment is excellent in improving the reliability, output characteristics, and durability of the power storage device.

[0274] In addition, it can be seen that the separators of Examples 1 to 29 have high whiteness and exhibit good voltage resistance compared to Comparative Examples 3, 4, and 6 containing metal oxides instead of ionic compounds. Furthermore, the capacity retention rate after 100 cycles of Examples 1 to 29 also exhibits a very high value compared to Comparative Examples 3, 4, 5, and 6. Therefore, the separator of the present embodiment is excellent in improving the reliability and durability of the power storage device.

[0275] It is clear from the above that a separator for an electricity storage device having a porous layer containing a polyolefin resin and an ionic compound and having a specific whiteness not only functions well as a separator but also contributes to improving the safety of the electricity storage device at high temperatures, and further can contribute to improving the output characteristics and durability of the electricity storage device.

Claims

1. A separator for a power storage device, comprising a porous layer containing a polyolefin resin and an ionic compound, wherein the content of the ionic compound in the porous layer is 5% by mass or more and less than 50% by mass, and the whiteness of the separator exceeds 98.0, and the polyolefin resin contains polyethylene having a viscosity average molecular weight of 600,000 or more and 5,000,000 or less, The whiteness is measured using a colorimeter with a 2° field of view without regular reflected light. The ionic compound has one or more anions selected from the group consisting of sulfate ions, nitrate ions, phosphate ions, and halide ions, and has one or more cations selected from the group consisting of alkali metal ions and alkaline earth metal ions.

2. The separator for an electric storage device according to claim 1, wherein The separator has a whiteness of 98.5 or more and 105 or less.

3. The separator for an electric storage device according to claim 1 or 2, wherein The content of the metal oxide in the separator for a power storage device is 10 mass % or less.

4. The separator for an electric storage device according to claim 1, wherein The ionic compound is barium sulfate.

5. The separator for an electric storage device according to claim 1, wherein The average particle size of the ionic compound is 5 nm or more and 600 nm or less.

6. The separator for an electric storage device according to claim 1, wherein The average pore diameter of the separator for a power storage device is 10 nm or more and 100 nm or less.

7. The separator for an electric storage device according to claim 1, wherein The electric storage device separator has an air permeability of 10 sec / 100 ml or more and 500 sec / 100 ml or less.

8. The separator for an electric storage device according to claim 1, wherein The electricity storage device separator has a puncture strength of 100 gf or more and 600 gf or less.

9. The separator for an electric storage device according to claim 1, wherein The polyolefin resin contained in the separator for a power storage device has a viscosity average molecular weight of 300,000 or more and 5,000,000 or less. 10 . An electric storage device comprising a positive electrode, a negative electrode, and the separator for an electric storage device according to claim 1 .

Citation Information

Patent Citations

  • Nonaqueous electrolyte battery, separator for it, and manufacture of the separator

    JP1998050287A

  • Separator for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery using it

    JP2005071979A

  • Separator for nonaqueous electrolyte battery and nonaqueous electrolyte battery

    JP2010262785A

  • Freestanding, heat resistant microporous film for use in energy storage devices

    WO2010108148A1

  • Ceramic separator and storage device

    WO2012005139A1